2020
DOI: 10.1515/jib-2020-0027
|View full text |Cite
|
Sign up to set email alerts
|

Cell – extracellular matrix interaction in glioma growth. In silico model

Abstract: The study aims to investigate the role of viscoelastic interactions between cells and extracellular matrix (ECM) in avascular tumor growth. Computer simulations of glioma multicellular tumor spheroid (MTS) growth are being carried out for various conditions. The calculations are based on a continuous model, which simulates oxygen transport into MTS; transitions between three cell phenotypes, cell transport, conditioned by hydrostatic forces in cell–ECM composite system, cell motility and cell adhesion. Visco-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 99 publications
(237 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, we also noticed a sharp correlation between all miRNAs and fatty acid biosynthesis in these tumors. These results showed that GPX7 -associated miRNAs dysregulated different pathways in gliomas, converging mainly to the regulation of the extracellular matrix, which has a dramatic influence on glioma invasiveness and aggressiveness 91 .…”
Section: Resultsmentioning
confidence: 88%
“…Furthermore, we also noticed a sharp correlation between all miRNAs and fatty acid biosynthesis in these tumors. These results showed that GPX7 -associated miRNAs dysregulated different pathways in gliomas, converging mainly to the regulation of the extracellular matrix, which has a dramatic influence on glioma invasiveness and aggressiveness 91 .…”
Section: Resultsmentioning
confidence: 88%
“…GBM shows that there is a robust cell–ECM interaction at play due to extensive ECM compositional alterations, stiffening, and mechanical stresses [ 20 , 98 ]. Here, the process and mechanism of how GBM cells sense this restructures ECM is defined through a couple of mechanosensors and their signaling pathways.…”
Section: Mechanobiology Of Gbm Cells: Adaptive Cellular Signaling Pat...mentioning
confidence: 99%
“…In addition, the movement of the cancer cells is further biased by various adhesionmediated process [54][55][56][57][58][59]. Due to the increasing evidence that gliomas induce a fibrous environment within the brain [72][73][74][75][76][77][78][79][80][81][82], in (1), we model the overall adhesion process using a non-local flux term that was introduced in [26] (see also [19,[27][28][29][30]49,83,84] for similar terms). Specifically, we explore the adhesive interactions of the cancer cells at x ∈ Ω(t) with other neighbouring cancer cells, with the distribution of the non-fibre ECM phase [85][86][87][88] as well as with the oriented fibre ECM phase [89,90], all located within a sensing region B(x, R) of radius R > 0.…”
Section: Cancer Cell Population Dynamicsmentioning
confidence: 99%